Local Guides' Experiences in Improving Speaking Skills Through Direct Interaction with Tourists in Lombok - Lailbarokah, Uzly; Kamaluddin; Azis , Atri Dewi (LITPAM, 2026)
This research was motivated by the fact that most local tour guides in Lombok developed their English speaking skills not through formal education or structured training, but rather through hands-on work experience. This phenomenon raises important questions about how this informal learning process can effectively improve speaking skills, given the frequent occurrence of grammatical and pronunciation errors that do not hinder communication. This study aims to describe how on-the-job experiences improve the English speaking skills of local tour guides in Lombok. A qualitative case study design was employed, with data collected through observation, in-depth interviews, and documentation from two tour guides at Han's Lombok Daily Tours, Senggigi, who had worked for at least five years and learned English primarily through work experience. The results of the study showed specific improvements in all five aspects of speaking skills. Fluency improved dramatically, from frequent pauses and nervousness to more fluent speech, although there were still brief pauses. Vocabulary expanded rapidly, from being very limited to being able to use informal expressions and new tourism terms such as